Islamic Corporate Governance (ICG) approach: An analysis of the implementation of asset utilization cooperation Case Study X University - Rizkia, Aisyah Putri (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
The X University is a public university with public service agency management and is transforming into a PTN BH. In the transition process, PTN X is required to manage its revenue to be financially independent. Once financially independent, PTN X must manage its revenue and operational costs and be released from government assistance. PTN X has carried out asset utilization cooperation, but from the auditor's findings, the asset utilization cooperation has yet to be profitable and even tends to lose. The cooperation has yet to be implemented according to good corporate governance management. Islam as a way of life can propose Islamic corporate governance as a foundation for managing PTN X cooperation services more responsibly using Islamic principles and ethics. Based on humans are creatures of God to be able to work according to the values taught by Islam. This research uses qualitative methods with in-depth interviews. This study aims to determine the implementation of asset utilization cooperation in terms of financial managers, leaders, and stakeholders. What are the obstacles in implementing asset utilization cooperation with the Islamic corporate governance approach, and analyze asset utilization cooperation in the accountability center corridor. The results showed that aspects of Islamic corporate governance have been carried out at PTN X. It's just that there are still many things that could be improved. Implementation must be based on rules, standard operating procedures, systemized and open. Responsibility center analysis is at the profit center level, where no profit calculation is outlined in the regulations. Suggestions for better management are to make standard operating procedures, rules, and systems more straightforward for managers and stakeholders, increase the professionalism of managers to advance asset service cooperation, increase revenue, and develop asset utilization cooperation with other businesses.